2017
DOI: 10.1111/jerd.12303
|View full text |Cite
|
Sign up to set email alerts
|

Loosening of the fixing screw in single implant crowns: predisposing factors, prevention and treatment options

Abstract: The problem of technical complications in implants and implant-supported restorations has existed for decades. The most frequent complication is the loosening of the fixing screw which, although is not catastrophic, if it occurs repeatedly, it may affect the success of the implant therapy and the patient satisfaction. Factors that affect the frequency of prosthetic complications include: the implant-abutment connection, para-functional habits, cantilevers and the type of restoration. The treatment options for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 78 publications
(170 reference statements)
1
61
0
2
Order By: Relevance
“…6,7 A number of studies have reported screw loosening is one of the major complications of dental implant therapy. 6,7 A number of studies have reported screw loosening is one of the major complications of dental implant therapy.…”
mentioning
confidence: 99%
“…6,7 A number of studies have reported screw loosening is one of the major complications of dental implant therapy. 6,7 A number of studies have reported screw loosening is one of the major complications of dental implant therapy.…”
mentioning
confidence: 99%
“…With respect to restoration designs, the splinted crown greatly reduced the screw loosening ratio compared to single crown. Factors that affect the screw loosening included: the implant‐abutment connection, cantilevers, the type of restoration and para‐functional habits . Bakaeen et al regarded that the screw loosening might be an early warning sign of biomechanical design problems or occlusal overload .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this outcome, we speculate that bone augmentation procedure screw loosening included: the implant-abutment connection, cantilevers, the type of restoration and para-functional habits. 40 Bakaeen et al regarded that the screw loosening might be an early warning sign of biomechanical design problems or occlusal overload. 41 Timely examination to tighten screws could recover the normal use for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cement‐retained restorations indicate more serious biological complications such as a more than 2 mm bone loss, while screw‐retained restorations display more technical problems such as screw loosening . Although screw loosening may occur in both types of restoration, screw‐retained restorations allow easy screw tightening, retrievability, and repair . Consequently, screw‐retained restorations seem to be more desirable than cement‐retained restorations …”
Section: Introductionmentioning
confidence: 99%
“…11 Although screw loosening may occur in both types of restoration, screw-retained restorations allow easy screw tightening, retrievability, and repair. 12 Consequently, screwretained restorations seem to be more desirable than cementretained restorations. 11 Several methods are proposed to facilitate the retrieval of cement-retained implant-supported restorations such as staining of the occlusal surface, 13 digital photography, 14 three-dimensional radiography, 15 and temporary cementation.…”
Section: Introductionmentioning
confidence: 99%